3x-4x+11=9

Simple and best practice solution for 3x-4x+11=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4x+11=9 equation:


Simplifying
3x + -4x + 11 = 9

Reorder the terms:
11 + 3x + -4x = 9

Combine like terms: 3x + -4x = -1x
11 + -1x = 9

Solving
11 + -1x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -1x = 9 + -11

Combine like terms: 11 + -11 = 0
0 + -1x = 9 + -11
-1x = 9 + -11

Combine like terms: 9 + -11 = -2
-1x = -2

Divide each side by '-1'.
x = 2

Simplifying
x = 2

See similar equations:

| 5-(x-8)= | | -7b-2=5b | | 6t-4=6t+6 | | 2y+42=7y | | -27+5x=7x+27 | | 11(67.66666667+-4.666666667y)+11y=220 | | 5x+7=-5-7x | | ln(-4-x)+ln(3)=ln(2-x) | | x^2-10=-x-8 | | 4x+2=13+3x | | 4y-2=9y+38 | | -8+3r=4r | | 5x+9=x+300 | | 4(1-4b)-4b=-96 | | 5x^2-6x+1=-5x+7 | | -7-8=10x+2-9x | | tan^2x-3tanx-2=0 | | -42=7(1-7x) | | 6-4(x+3)=9x+7-5x | | 3x+3=100-4x | | 7x+8x-96=120-9x | | 4x+7+2x=2(3x-3) | | -3y-19=-1 | | -8q+1+3q=10-6q | | 4m+5=2-9 | | 4z+3x= | | 0.55+0.27t=2.34t-0.83 | | F=amforM | | 629.35=41(x+2.35) | | 4(y+14)-8=72 | | 5x^2-13x-9=-5x-5 | | 6n+21=87 |

Equations solver categories